2002
DOI: 10.1046/j.1444-2906.2002.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of phosphorus absorption from several feed ingredients in rainbow trout during growing stages and effect of extrusion of soybean meal+

Abstract: The absorption of phosphorus (P) contained in several feed ingredients by rainbow trout was compared during the growing stages of the fish. The ingredients tested were pollock meal, sardine meal, poultry feather meal (PFM), meat and bone meal (MBM), defatted soybean meal (SBM), soy protein concentrate (SPC), corn gluten meal (CGM), and defatted soybean meal extruded at 150°C (exSBM). Phosphorus absorption was determined for fish of sizes 2 g, 5 g, 10 g, 20 g, 50 g, 100 g, and 200 g. Absorption of P from the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…The difference is probably due to fish species, fish size, diet composition, phosphorus sources and culture system (Schwarz, 1995;Shearer, 1984Shearer, , 1995Shearer, , 2000El-Zibdeh et al, 1995b;Riche and Brown, 1999;Avila et al, 2000;Lall and Vielma, 2001;Satoh et al, 2002). On the other hand, the difference is also due to the response criteria and statistical method/model employed in these studies ( Figs.…”
Section: Discussionmentioning
confidence: 72%
“…The difference is probably due to fish species, fish size, diet composition, phosphorus sources and culture system (Schwarz, 1995;Shearer, 1984Shearer, , 1995Shearer, , 2000El-Zibdeh et al, 1995b;Riche and Brown, 1999;Avila et al, 2000;Lall and Vielma, 2001;Satoh et al, 2002). On the other hand, the difference is also due to the response criteria and statistical method/model employed in these studies ( Figs.…”
Section: Discussionmentioning
confidence: 72%
“…Phosphorus is an essential macro mineral in fish diets. Its deficiency causes poor growth and bone deformities, and in excess it inhibits zinc utilization (Satoh et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, higher inclusions of soy products may be limited by low availability of other nutrients such as methionine (Perkins 1995) and phosphorus (Satoh et al 2002). Phosphorus is an essential macro mineral in fish diets.…”
Section: Introductionmentioning
confidence: 99%
“…Satoh et al (2002) reported that in rainbow trout, P absorption from fishmeal decreased slightly as body weight increased. This was in contrast to P curred at 8-h post-feeding and tended to exceed the effect of feeding control IP diet.…”
Section: (Asda Laining)mentioning
confidence: 99%